Dispensing Patterns of Blood Pressure Lowering Agents in Older Australians From 2006 to 2016. (May 2019) - Si, Si; Ofori-Asenso, Richard; Briffa, Tom; Ilomaki, Jenni; Sanfilippo, Frank; Reid, Christopher M.; Liew, Danny
Background: Increasing numbers of blood pressure lowering (BPL) agents are being prescribed for both primary and secondary prevention of cardiovascular disease, especially in the older population. The aim of this study is to describe the temporal trends and patterns of BPL dispensing among older Australians (aged ≥65 years). Methods: We utilized prescription claims data from the Australian Pharmaceutical Benefits Scheme (PBS) for a 10% random sample of people aged ≥65 years. The PBS, funded by the Federal government, provides subsidies to make medicines more affordable for Australian residents. We restricted our analysis to "long-term concession" individuals, who would use PBS for the majority of their medication needs. BPL agents were identified using the World Health Organization Anatomical Therapeutic Chemical classification codes. The annual prevalences and proportional distributions of BPL dispensing by categories were summarized from 2006 to 2016. Direct standardization was applied to indicate changes of BPL dispensing over time. Results: Age-standardized dispensing of BPL agents increased by 8% among older Australians from 2006 to 2016 (58%-66%). BPL dispensing in males has exceeded that in females since 2009. Angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers were the dominant BPL agents dispensed, with more than 55% of all BPL users over time. Dispensing of diuretics decreased from 27% to 21%, calcium channel blockers decreased from 30% to 25%, while β-blockers remained stable (29%-31%). The use of fixed-dose combinations increased over time from 23% to 31%. Conclusion: The prevalence of BPL dispensing steadily increased among older Australians from 2006 to 2016. The changes in the patterns of BPL dispensing were largely in line with contemporary changes to clinical guidelines for an aging population.